Examining the relationship between hope and life satisfaction among middle school students - Abdi Gungor; Mehmet Avci (Journal of Pedagogical Research, 2017)
Life satisfaction has received a vast amount of attention in positive psychology. The importance of life satisfaction in education has also been emphasized for students' comprehensive development. In this regard, it is crucial to understand factors related to a student's life satisfaction for their mental, social, and academic development. Positive psychology highly focuses on hope, and hope has been found related to desirable outcomes. However, it is still not known the role of hope in life satisfaction for Turkish middle school students. The main goal of this study was to examine hope's prediction of life satisfaction in middle school students. This study also aimed to investigate differences in students' life satisfaction based on their gender and grade levels. Data were collected from 339 middle school students attended three public middle school located in the west of Turkey.  The findings of the study revealed that hope significantly predicted family (R2 = .21), school (R2 = .24), friend (R2 = .24), self (R2 = .40), living environment (R2 = .13), and total (R2 = .43) life satisfaction scores. The results also showed that girls had higher scores on life satisfaction than boys in school, friend, living environment, and total life satisfaction scores whereas no difference was observed in family and self-satisfaction scores. Regarding grade level, significant differences were found in family, school, self, and total life satisfactions scores. According to post-hoc comparisons, 8th graders reported lower level of life satisfaction. No differences were found in friend and living environment satisfaction scores based on gender. The results with implication for future research and practice are discussed.